Leads directions of pud water supply and wastewater - Старостіна, Альона Юріївна (Eastern-European Journal of Enterprise Technologies, 2011)
The mechanism of forming of row of alternative directions of development of communal enterprise is considered with the use of SWOT- analysis, and also possibility of application of matrix of influencing of alternatives for the sake of choice most priority from them